2016
DOI: 10.18321/ectj433
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Benzene, Toluene, Ethylbenzene and o-Xylene by Carbon-Based Adsorbents

Abstract: This study explored the possibility of applying different carbon-based adsorbents for removal of benzene, toluene, ethylbenzene and o-xylene (BTEX) from indoor air in static and dynamic modes. To determine BTEX removal effectiveness, the approach based on solid-phase microextraction (SPME) in combination with gas chromatography -mass spectrometry (GC-MS) was used. In static mode, removal effectiveness of BTEX from indoor air using different carbon-based adsorbents (shungite, walnut shell, saxaul, apricot pits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
2
0
0
Order By: Relevance
“…Toluene (77%) and benzene (53%) were sorbed significantly within one day of hydrocarbon addition ( Figure S1 ) compared to those without Tenax-TA (representing 100% of available hydrocarbons). This result was consistent with other studies of benzene and toluene adsorption [ 46 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Toluene (77%) and benzene (53%) were sorbed significantly within one day of hydrocarbon addition ( Figure S1 ) compared to those without Tenax-TA (representing 100% of available hydrocarbons). This result was consistent with other studies of benzene and toluene adsorption [ 46 ].…”
Section: Resultssupporting
confidence: 94%
“…Raw DE is capable of adsorbing all BTEX hydrocarbons; studies have found in a BTEX mixture, xylenes were more readily sorbed to DE while benzene sorbed the least [ 56 ]. Previous findings have shown that Tenax-TA is capable of adsorbing approximately 78% of benzene and 99% of toluene [ 46 ], which is comparable albeit slightly higher than our abiotic results (53–77% adsorption; Figure S1 ).…”
Section: Resultssupporting
confidence: 82%